Inventory Management System Olahan Hasrat Sdn. Bhd. Using Mobile Application - Fadhlul Hilmy Musa; Rosziati Ibrahim (Applied Information Technology And Computer Science, 2021)
The Inventory Management System (IMS) is commonly used in industry today to improve the productivity of item movement. In order to have a proper business that involves with large amount of goods or items, a strong fundamental need to be worked behind the scene which can affect a company rate of work and budget. The old IMS approach included a lot of paperwork, such as spreadsheet and order list, which would be more difficult to handle as storage increases. The inventory management system can then be computerized to further improve the productivity of IMS. The goal of this project is to build IMS software which can store a large amount of item data. The main component of this system is to track the inventory that is going in and out from the warehouse. Other than that, this mobile application can store project calculation and see the report of monthly spending. In addition, the system can also compare prices between suppliers with the latest price of the goods from online shops. In order to develop the software, the methodology of the project is approached by using prototype model. Firstly, the requirements of the software are defined, followed by the choice of software development tools to develop the software that can satisfy the criteria of the software. The program will then be built and debugged. This paper focuses on designing IMS with mobile application for Small Medium Enterprise (SME) and the use of engineering companies in the field.